Evaluation of methods and marker systems in genomic selection of oil palm (Elaeis guineensis Jacq.) - Kwong, Qi Bin; Teh, Chee Keng; Ong, Ai Ling; Chew, Fook Tim; Mayes, Sean; Kulaveerasingam, Harikrishna; Tammi, Martti; Yeoh, Suat Hui; Appleton, David Ross; Harikrishna, Jennifer Ann (BioMed Central, 2017)
Background